Educação do campo e participação social: reflexões sobre a experiência da Casa Familiar Rural de Cametá/PA - PRAZERES, Maria Sueli Corrêa dos (2008)
The thesis aimed to reflect on the experience of the Cametá's Rural Familiar House. In the broad sense the search sought investigate the contributions of experience to the subject of the rural áreas of Cametá. In particular meaning as it aimed to analyze the participation of the subjects in the dynamics of Cametá's Rural Familiar House; identify it's mechanisms used by to motivate the participation of the subject and identify it's contributions, to the vision of Cametá subjects who participate directly or indirectly from the experience. Thus, the study followed the perspective of qualitative approach to research, using the semi-structured -interviews with young people, parents, tutors, teachers, coordinating educational, egresso, representatives of social movements and community members; and documental analysis examining the referential giving legal support to the experience of Cametá's Rural Familiar House. The study allowed On one hand, that the experience of Cametá's Rural Familiar House is significant and extremely important for young people, since the contents are organized from the reality of them. Thus, it was possible to identify that the proposal assentada in Pedagogy of Alternância can be a viable alternative to the educational field cametaense. According to the subjects interviewed were unable to perceive that there is an effort to have the integration and participation of the school / family /community education in the dynamics of the Cametá's Rural Familiar House. However, despite this effort there are many constraints that limit an ampler participation of the subjects, among whom the socioeconomic condition of families and the community, the loss of financial autonomy of the Cametá's Rural Familiar House and location of the school in a distant axis of families. Despite the difficulties there is a significant contribution of the Cametá's Rural Familiar House for youth of the rural áreas of Cametá since it is seen by subject as a chance to strengthen the education of rural areas, the strengthening of the production units with the introduction of techniques related to family farming and the strengthening of community in the fight for the legitimacy of social rights. Moreover, the survey intend to contribute to the Paraense Movement For Rural Education to recognize and question many experiences created by this social movements, lifting theoretic elements to this theoretical.